Standardized Diagnostics Including PET-CT Imaging, Bilateral Tonsillectomy and Neck Dissection Followed by Risk-Adapted Post-Operative Treatment Favoring Radio-Chemotherapy Improve Survival of Neck Squamous Cell Carcinoma of Unknown Primary Patients - Wichmann, Gunnar; Willner, Maria; Kuhnt, Thomas; Kluge, Regine; Gradistanac, Tanja; Wald, Theresa; Fest, Sandra; Lordick, Florian; Dietz, Andreas; Wiegand, Susanne; Zebralla, Veit (Frontiers in Oncology, 2021)
Background: About five to 10% of cancers in the head and neck region are neck squamous cell carcinoma of unknown primary (NSCCUP). Their diagnosis and treatment are challenging given the risk of missing occult tumors and potential relapse. Recently, we described human papilloma-virus (HPV)-related NSCCUP-patients (NSCCUP-P) as a subgroup with superior survival. How-ever, standardized diagnostic workup, novel diagnostic procedures, decision-making in the multi-disciplinary tumor board (MDTB) and multimodal therapy including surgery and post-operative radio-chemotherapy (PORCT) may also improve survival. Methods: For assessing the impact of standardized diagnostic processes simultaneously established with the MDTB on outcome, we split our sample of 115 NSCCUP-P into two cohorts treated with curative intent from 1988 to 2006 (cohort 1; n=53) and 2007 to 2018 (cohort 2; n=62). We com-pared diagnostic processes and utilized treatment modalities applying Chi-square tests, and out-come by Kaplan-Meier plots and Cox regression. Results: In cohort 2, the standardized processes (regular use of [18F]-FDG-PET-CT imaging fol-lowed by examination under anesthesia, EUA, bilateral tonsillectomy and neck dissection, ND, at least of the affected site) improved detection of primaries (P = 0.026) mostly located in the oro-pharynx (P = 0.001). The from 66.0% to 87.1% increased ND frequency (P = 0.007) increased the detection of extracapsular extension of neck nodes (ECE+) forcing risk factor-adapted treatment by increased utilization of cisplatin-based PORCT that improved 5-years progression-free and overall survival from 60.4% and 45.3% to 67.7% (P=0.411) and 66.1% (P=0.025). Conclusions: Standardized diagnostic workup followed by ND and risk-factor adapted therapy improve survival of NSCCUP-P.